Experimental evidence of exciton capture by mid-gap defects in CVD grown monolayer MoSe2 - Ke Chen (Nature Portfolio, 2017)
Mid-gap defects: Carriers in a trap The temporal dynamics of photo-generated electrons and holes in MoSe2 trapped by defects are revealed. While transitional metal dichalcogenides have significant potential for optoelectronic applications, samples tend to contain defects such as vacancies and impurities, most of which affect carrier mobility by inducing mid-gap states, i.e. within the bandgap. Now a team led by Yaguo Wang from the University of Texas elucidates the role of defects in samples grown by chemical vapor deposition. Femtosecond pump probe spectroscopy reveals that such defects are prone to capture (within few picoseconds) and then release (at slightly longer timescales of hundreds of picoseconds) electrons and holes. Such dynamics are intrinsic to samples grown with this particular method and possibly linked to the oxygen-associated impurities introduced during growth. This knowledge is relevant to engineering the properties of 2D materials for optoelectronics applications.